Rain fade slope analysis for terrestrial microwave link in Malaysia - Islam, Md. Rafiqul; Dao, Hassan; Zayuod, Al Hareth (2009)
This paper analyzes fade slope during raining events based on measured data on terrestrial microwave link in Kuala Lumpur operating at 15GHz and 23 GHz. Fade slope is examined on a statistical basis for the two sites. The annual statistics of fade slope are presented and compared to Van de Kamp model which is recommended by ITU-R.